Zakat dalam Perekonomian Modern: Aspek Mikro dan Makro: Zakat in the Modern Economy: Micro and Macro Aspects - Khaerul Aqbar (Litera Academica Publishing, 2024)
This study aims to describe the role of zakat in the modern economy with a focus on micro and macroeconomic aspects. This study uses a qualitative approach with a descriptive-analytical method. The results of this study indicate that zakat plays an important role in the modern economy, both from micro and macro aspects. From a microeconomic perspective, zakat functions as an income redistribution mechanism that increases aggregate consumption, especially through the transfer of wealth from the rich (muzaki) to the poor (mustahik). From a macroeconomic perspective, zakat has the potential to increase national savings and encourage investment in the real sector. Because zakat is imposed not only on income but also on idle wealth, it provides incentives for muzaki to invest their wealth productively, which can increase aggregate production in the economy. Overall, effective implementation of zakat can be a powerful instrument to address socio-economic disparities, improve the quality of consumption, and encourage more inclusive and sustainable economic growth. In the context of Islamic economics, zakat is not only a religious obligation but also an important tool for achieving social justice and the welfare of society as a whole.